Followership in nurses working in Saudi Arabian hospitals: A cross‐sectional study. Issue 6 (2nd September 2022) - Alanazi, Sulaiman; Wiechula, Richard; Foley, David
Abstract: Aim: To explore the followership styles and their associations with nurses' sociodemographic profiles in Saudi Arabia. Background: In Saudi Arabia, nurses' role is seen as less important and passive. However, whether they were actually passive followers has not been examined. No previous research has examined nurses' followership styles in Saudi Arabia. Methods: This cross‐sectional study used a convenience sample of nurses. The Kelley followership questionnaire‐revised was used to determine the prevalence of the five followership styles. Participants' demographic characteristics, which included age, gender, nationality, education level, years of experience, and role, were collected to investigate their associations with followership styles. An online survey was designed and distributed using SurveyMonkey®. Data were analyzed with logistic regression and expressed as odds ratios. Results: This study included 355 nurses. Findings revealed that the predominant followership style was exemplary (74%), followed by the pragmatist (19%), conformist (4%), and passive styles (3%). Logistic regression analysis revealed that expatriates, higher education, and a leader role had an independent association with an exemplary followership style. Male gender was associated with a passive style. Younger age, male gender, Saudi Arabian nationality, undergraduate qualification, no previous leadership experience, a follower role, and fewer years of experience increased the odds of having a pragmatist style. Conclusion and Implications: Followership styles were influenced by sociodemographic and work‐related factors. Young nurses with less experience tend to be pragmatist followers. Nursing managers should integrate followership styles when planning leadership and team development courses to ensure maximum team effectiveness as leadership and followership are interdependent.